Apoptotic and non-apoptotic cell death induced by cis and trans analogues of a novel ammine(cyclohexylamine)dihydroxodichloroplatinum(IV) complex - O'Neill, C F; Ormerod, M G; Robertson, D; Titley, J C; Cumber-Walsweer, Y; Kelland, L R (British journal of cancer, 1996)
It has been previously demonstrated that cisplatin induces apoptosis in the CH1 human ovarian carcinoma cell line. This study demonstrates that two novel platinum (Pt) analogues JM149 and JM335, which are the cis and trans geometry respectively of ammine(cyclohexylamine)dihydroxodichloroPt(IV), initiate apoptosis in this cell line at physiologically relevant concentrations (IC50 values 2 h drug exposure were 35.3 microM for JM149 and 18.7 microM for JM335). While at equimolar drug concentrations there was a 2-fold higher level of total platinum-DNA adducts following exposure to JM335 vs JM149, at equitoxic concentrations, levels were similar (80 vs 70 pmol Pt mg-1 DNA respectively). Following a 2 h incubation with 2 x IC50 of both drugs, cells rounded up and detached in a time-dependent manner but with the kinetics of apoptosis being more rapid for JM335. The majority of detached cells exhibited morphology associated with apoptosis which was further supported by the presence of a 50 kb fragment detected in DNA lysates prepared from these cells. JM149 induced apoptosis across a range of concentrations (2 x, 5 x and 10 x IC50) with a 50 kb DNA fragment being detected at all concentrations. However, in marked contrast to this, JM335 failed to cause apoptosis at 10 x IC50, the detached cells neither displaying apoptotic morphology nor a detectable 50 kb DNA fragment. Moreover, these detached cells showed evidence of extensive vesiculation while the DNA remained normal in appearance and thus appeared to have died by a non-apoptotic mode. Apoptosis also appeared to be induced to a lesser extent at 5 x IC50 of JM335 as demonstrated by a less intense 50 kb fragment compared with that seen at 2 x IC50. The main cell cycle effect of these drugs (at 2 x IC50) was a slowdown in S-phase traverse during which most but not all of the apoptosis appeared to occur. However, at 5 x IC50 of JM335 cells appeared frozen in all phases of the cell cycle with little progress from G1 to S accompanied by a build-up of cells in G2 indicative of a G2/M block. This difference in cell cycle effect may account for the reduced level of apoptosis at this concentration and a failure to engage apoptosis at higher concentrations. These data suggest that the nature of the platinum drug (and consequently, the nature of resultant DNA damage) may have important implications in determining the rate and mechanism of cell death in this cell line. The cell death effects observed with the trans complex JM335 may correlate with the induction of DNA single-strand breaks in this cell line.